Development assistance for health in central and eastern European Region - Marc Suhrcke; Bernd Rechel; Catherine Michaud (The World Health Organization, 2005)
OBJECTIVE: We aimed to quantify development assistance for health to countries of central and eastern Europe and the Commonwealth of Independent States (CEE-CIS). METHODS: We used the International Development Statistics database of the Organisation for Economic Co-operation and Development and the database on development assistance for health compiled for the Commission on Macroeconomics and Health to quantify health development assistance to the region, compared to global and overall development assistance. We based our analysis on standard health indicators, including child mortality, life expectancy at birth and health expenditures. FINDINGS: Although total development assistance per capita to CEE-CIS was higher than that for most other regions of the world, development assistance for health was very low compared to other countries with similar levels of child mortality, life expectancy at birth and national expenditures on health. CONCLUSION: The allocation of development assistance for health on a global scale seems to be related far more to child mortality rather than adult mortality. Countries of CEE-CIS have a high burden of adult morbidity and mortality from non-communicable diseases, which does not appear to attract proportionate development assistance. Levels of development assistance for health should be determined in consideration of the region's particular burden of disease.